Clinical outcomes of COVID-19 patients with solid and hematological cancer: a meta-analysis and systematic review - Joni Wahyuhadi, Joni
Abstract Background: Previous research has consistently shown the significant difference in outcome between cancerous and non-cancerous patients with coronavirus disease 2019 (COVID-19). However, no studies have compared the clinical manifestation of COVID-19 in hematologic cancers patients and solid cancers patients. Therefore, we analyzed the outcome of COVID-19 patients with hematological cancer and primary solid cancer worldwide through a meta-analysis and systematic review. Methods: This meta-analysis and systematic review included English language articles published between December 2019 – January 2021 from Pubmed and Google Scholar. The Newcastle Ottawa Score was used to assess the quality and bias of included studies. The outcome measures were case-fatality rate and critical care events for COVID-19 patients with cancer and comorbidities. Results: The initial search found 8910 articles, of 20 were included in the analysis. Critical care events and mortality were higher in the hematological than primary solid cancer group (relative risk (RR)=1.22 & 1.65; p <0.001). Conversely, mortality was lower in patients with two or fewer comorbidities (RR=0.57; p<0.001) and patients under the 75-year-old group (RR=0.53; p< 0.05). Conclusions: Hematologic malignancy, age, and the number of comorbidities are predictor factors for worse prognosis in COVID-19 infection.